Debit card interchange fees generally lead to cash-promoting cross-subsidisation - Harry Leinonen (Bank of Finland, 2011)
Cards and cash are competing payment instruments at point-of-sale. The twosided market platform theory, based on general benefit assumptions, supports the use of multilateral interchange fees for card payments as a means of promoting the use of cards. However, analysis of the issue from the concrete processing cost viewpoint leads to the opposite conclusion: collection of debit card interchange fees by issuers results in subsidisation of cash and so actually promotes the use of cash instead of cards. Banks use card interchange revenues to cover cash distribution costs. For merchants, interchange fees increase payment costs and thus reduce the possibilities to pass through to customers the cost savings flowing from card efficiency. Moreover, because of high merchant fees due to high interchange fees, merchants are also more reluctant to accept payment cards. An MIF based on the tourist level approach will result in all parties being indifferent between cash and cards and thereby delay the realisation of the cost benefits of increased debit card usage. The resent actions of authorities to increase transparency and reduce cross-subsidisation seem to point in the right direction towards more efficient resource allocation in payments.
URN:NBN:fi:bof-20140807213
Keywords: 330